Surgical management of recurrent idiopathic pneumatosis intestinalis in the pediatric population - Shannon N. Acker; Sarah Ogle; Jessica Saifee; Lucas Marks; Ann M. Kulungowski (Elsevier, 2021)
Pneumatosis intestinalis (PI) is the presence of air in the bowel wall that can occur as the result of many different etiologies. PI remains difficult to treat as it can indicate severe compromise of the intestine, such as occurs in necrotizing enterocolitis (NEC) in premature infants, or it can be a relatively benign finding with little clinical sequelae. In general, PI is treated with bowel rest and broad-spectrum antibiotics regardless of the underlying etiology. This approach leads to resolution of PI in the majority of cases. However, in some cases, the PI recurs despite repeated or prolonged medical therapy and bowel rest. There are no standard guidelines to facilitate management in these cases. This is a case series of children with neurologic impairment who had recurrent PI. Each of these children were successfully treated with operative intervention in the form of diverting ileostomy (n = 2) or colectomy with ileostomy (n = 2)